COVID-19 VACCINATION: BETWEEN STATE RESPONSIBILITIES AND COMMUNITY HUMAN RIGHTS - Situmeang, Tomson; Panjaitan, Hulman; Lengkong, Lonna Yohanes (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The Covid-19 pandemic around the world has preoccupied all countries in the world with various strategies to overcome and or minimize the spread of the Covid-19 virus. Indonesia promotes Covid-19 vaccination for all Indonesian people as the responsibility of the state to protect and guarantee the health services of its citizens. Pros and Cons of Covid-19 Vaccination is a challenge for the state in carrying out its obligations. The Covid-19 vaccination is the responsibility of the state as well as the fulfillment of the community's human rights to health services and insurance, so that the implementation of the Covid-19 vaccination is required by the state for all citizens in order to protect public health more thoroughly. This research uses a form of normative legal research by identifying or taking an inventory of legal principles or principles with the statute approach method, namely examining the provisions of laws and regulations related to the legal issues to be studied. From the research conducted, vaccination is the responsibility of the state in order to protect the health of citizens as a human right of the community.